Simultaneous Determination of Organochlorine Pesticides, Polycyclic Aromatic Hydrocarbons and Polychlorinated Biphenyls in Water by Solid Phase Disk Extraction-Ultrasonic Desorption and GCMS - Li, X.Y.; Zhang, Y.T.; Zhang, L.; Gui, J.Y.; Zhang, C.L. (Asian Journal of Chemistry, 2015)
A method was developed for the simultaneous determination of organochlorine pesticides, polycyclic aromatic hydrocarbons and polychlorinated biphenyls in water by solid-phase disk extraction-ultrasonic desorption and gas chromatography-mass (GC-MS).The samples were extracted by C18 solid-phase disk extraction, and ultrasonic wave to promote the extraction of object from the solid phase membranes, which realize the simultaneous purification of 17 types organochlorine pesticides, 16 kinds of polycyclic aromatic hydrocarbons and 2 kinds of aroclors. The recoveries of the compounds of this method were 70-130 %, with relative standard deviation below 10 and the detection limit between 0.2 and 1.1 ng/L, which would satisfy the demand of daily water quality analysis.